Development of Bi2S3 thin film solar cells by close-spaced sublimation and analysis of absorber bulk defects via in-depth photoluminescence analysis - Koltsov, M.; Gopi, S.V.; Raadik, T.; Krustok, J.; Josepson, R.; Gržibosvkis, Raitis; Vembris, Aivars; Spalatu, N. (Elsevier, 2023)
The emergence of new PV applications in society requires the design of new materials and devices based on green and earth-abundant elements, with a different set of properties and wider applicability. In this perspective, Bi2S3 semiconductor material have gained attention as a defect-tolerant, non-toxic, and highly stable material for earth-abundant thin film PV technologies. Related to Bi2S3 non-toxic nature, so far it has been very popular to synthesize the material by chemical solution routes, while little research efforts have been dedicated to absorber deposition by physical deposition techniques. In particular, there are no studies on absorber development via rapid, high-volume, and in-line close-spaced sublimation technique. Moreover, in-depth analysis of material defects employing low temperature-dependent photoluminescence (PL) remains largely unexplored. In this work, we systematically study the impact of close-spaced sublimation (CSS) conditions on Bi2S3 absorber growth on various substrates, employing a wide range of source (400–600 °C) and substrate (200–400 °C) temperatures. CSS source temperature of 550 °C and substrate temperature of 400–450 °C were identified as optimal temperatures (grown either on glass, TiO2, or CdS substrates), allowing the fabrication of uniform and dense Bi2S3 films with enhanced [221]-oriented grains. For the first time, a proof of concept solar cell with CSS Bi2S3 is demonstrated and an in-depth analysis on the interrelation between grain structure, interface recombination, and device performance is provided. Employing low-temperature dependence PL, new and complementary insights on possible defects and recombination mechanisms are presented.--//-- M. Koltsov, S.V. Gopi, T. Raadik, J. Krustok, R. Josepson, R. Gržibovskis, A. Vembris, N. Spalatu, Development of Bi2S3 thin film solar cells by close-spaced sublimation and analysis of absorber bulk defects via in-depth photoluminescence analysis, Solar Energy Materials and Solar Cells, Volume 254, 2023, 112292, ISSN 0927-0248, https://doi.org/10.1016/j.solmat.2023.112292.(https://www.sciencedirect.com/science/article/pii/S0927024823001137) Published under the CC BY-NC-ND licence.
This study was funded by the Estonian Research Council projects PSG689 “Bismuth Chalcogenide Thin-Film Disruptive Green Solar Technology for Next Generation Photovoltaics”, PRG627 “Antimony chalcogenide thin films for next-generation semi-transparent solar cells applicable in electricity producing windows”, and PRG1023; the Estonian Centre of Excellence project TK141 (TAR16016EK, TAR16016) “Advanced materials and high-technology devices for energy recuperation systems”, and the European Union's H2020 programme under the ERA Chair project 5GSOLAR grant agreement No 952509.
Keywords: Bismuth sulfide; Close-spaced sublimation; Thin film solar cells; Deep defects; Low-temperature dependence photoluminescence